Model Object Relational Database pada Aplikasi Notifikasi Sms - Indrajani, Indrajani (Bina Nusantara University, 2013)
The purpose of this research is to analyse the database using object oriented approach. In addition, this research develops and designs an object relational database structure to make easier the process of searching for the required information. The benefit of this research is to provide a data structure that can be reused for SMS notification application developer team, so that the developers can use existing objects for future use if there are changes in the current business process. The methods used are data collection, analysis, and design. The result obtained from this research is a database structure of sms notification application, which can be used in various programming languages for using object relational database approach. For conclusion, by using the object relational database structure, application developers will be made easier in developing the current database structure. Programmer can add a new data type simply by creating a new object. Data is accessed or processed as object-oriented.